Computational evaluation on spectroscopic (FT-IR, Raman), electronic and biological, and NLO properties of cirsilineol by DFT, ADMET, and molecular docking method - Tirth Raj Paneru; Poonam Tandon; Bhawani Datt Joshi (Bibechana)
Cirsilineol is a natural product that has pharmacological characteristics and is used to prevent the growth of cancer. This study aims to investigate the spectroscopic, electronic, and biological properties of drugs and predict their suitability for drug-like candidates to inhibit prostate cancer. The computational evaluation was performed with density functional theory (DFT) at B3LYP/6−311++G(d,p) level of theory and drug-like characteristics rendered from ADMET analysis. Spectral measurement for IR and Raman provided evidence of intra-molecular hydrogen bonding of the OH group in ring R1. The electronic transition properties of the title compound were determined using TD-DFT with a polarized continuum model in solvent ethanol, resulting in a blue shift in absorption wavelength. The electrostatic potential mapped with the van der Wall surface predicted effective electrophiles and nucleophiles, allowing for the layout of intra- and intermolecular hydrogen bonds. The pharmacological properties of cirsilineol determined by ADMED analysis confirmed that it is non-toxic. To assess the biological performance of cirsilineol, molecular docking was performed with protein codes 1E3G and 1GS4, which showed inhibition action with binding affinity −7.7 and −7.8 kcal/mol, respectively.